Development of methyl isoxazoleazepines as inhibitors of BET. Issue 9 (1st May 2015) - Hewitt, Michael C.; Leblanc, Yves; Gehling, Victor S.; Vaswani, Rishi G.; Côté, Alexandre; Nasveschuk, Christopher G.; Taylor, Alexander M.; Harmange, Jean-Christophe; Audia, James E.; Pardo, Eneida; Cummings, Rich; Joshi, Shivangi; et al.
Graphical abstract: Abstract: In this report we detail the evolution of our previously reported thiophene isoxazole BET inhibitor chemotype exemplified byCPI-3 to a novel bromodomain selective chemotype (the methyl isoxazoleazepine chemotype) exemplified by carboxamide23 . The methyl isoxazoleazepine chemotype provides potent inhibition of the bromodomains of the BET family, excellent in vivo PK across species, low unbound clearance, and target engagement in a MYC PK-PD model.